2003
DOI: 10.1002/micr.10098
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable, thermosensitive implant for approximating cylindrical structures: A preliminary study

Abstract: A new invention, i.e., a biodegradable, thermosensitive hybrid gel composite in the form of a thin sheet, was used as an implant inside the rat and guinea pig to test its tissue reactions, degradation, and function as a bridging agent. Tissue tractions in subcutaneous tissue, in muscle, around a peripheral nerve, and around an artery were mild. Degradation made rapid progress, starting on the third day and completed in 2-3 weeks. The hybrid gel, when wrapped around the cut ends of a peripheral nerve or an arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…[22][23][24] Namely, above 32 C, PNIPAM becomes insoluble in water so that the gel network made of such a polymer expels water and collapses. Upon lowering the temperature, individual microgels can swell up to 10 times in their size.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24] Namely, above 32 C, PNIPAM becomes insoluble in water so that the gel network made of such a polymer expels water and collapses. Upon lowering the temperature, individual microgels can swell up to 10 times in their size.…”
Section: Introductionmentioning
confidence: 99%
“…Among environmentally sensitive polymers, thermally sensitive poly( N -isopropylacrylamide) (PNIPAM) with a lower critical solution temperature (LCST ∼32℃) is the mostly studied. 2224 Namely, above 32℃, PNIPAM becomes insoluble in water so that the gel network made of such a polymer expels water and collapses. Upon lowering the temperature, individual microgels can swell up to 10 times in their size.…”
Section: Introductionmentioning
confidence: 99%
“…16 Another in vivo study showed that pNIPAM is safe and effective in approximating cylindrical structures such as peripheral nerve and artery without any toxic effects. 17 Our in vivo study showed that ppNIPAM-coated implants may stay attached to the retina for at least 6 weeks. It is often difficult but critical to remove the posterior vitreous totally from the retinal surface, especially in rabbits, because when we leave a residual vitreous the ppNIPAM coated implant may loosen from the retinal surface.…”
Section: Discussionmentioning
confidence: 71%